Surgery of Severe Cauliflower Ear Deformity - Indri Lakhsmi Putri, MD, PhD; Melia Bogari, MD; Auliai Khoirunnisa, MD; Faizal Rezky Dhafin, B.Des; Djoko Kuswanto, B.Eng (Plastic and Reconstructive Surgery, Global Open, 2023)
A cauliflower ear is an auricular deformity characterized by thickened soft tissue and cartilage. A subperichondrial hematoma or fluid collection causes this malformation. As a result of being cut off from the perichondrium blood supply, the ear cartilage becomes ischemic, developing scar tissue, fibrous tissue, new cartilage overgrowth, or necrosis beneath the skin, resulting in a permanent alteration in the shape of the external ear resembling that of a cauliflower. To properly fix defects, the surgeon must grasp ear anatomy and be familiar with a variety of reconstructive alternatives. It requires meticulous attention, due to the intricate design of the ear. Simple and complex techniques for treating cauliflower ears have been developed. However, in severe cases, simple techniques are often insufficient. As a result, complex techniques such as replacement with an auricular prosthesis or implant or autogenous costal cartilage framework were developed. We present a case of a 25-year-old man who experienced a severe cauliflower ear as a result of an infection during adolescence. The patient was concerned about the shape of his ear and was depressed. Ear reconstruction was accomplished using the costal cartilage framework engraved according to a three-dimensional cutting guide for surgical planning. Costal cartilage is chosen to provide a framework for reconstruction as it is strong and rigid, and its curved shape is similar to that of the external ear. There were no complications after surgery. The ear projection and shape have performed admirably. The patient was pleased with the outcome and felt more confident after surgery.